Implementation of the Concept of Democracy in the World of Learning at Elementary School Level - Jemma Sar; Wanda Haroa (Cattleya Darmaya Fortuna, 2025)
The application of the concept of democracy in the world of learning at the Elementary School (SD) level is an important step in forming the character of students who are critical, responsible, and respectful of differences. Democratic education does not only emphasize the delivery of teaching materials, but also on a participatory, dialogical learning process, and respect for students' rights and voices. This study aims to examine how democratic principles are integrated into learning activities in elementary schools, the role of teachers in creating a democratic learning environment, and its impact on students' attitudes and behavior. The method used in this study is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the application of democracy in learning can increase student activity, strengthen tolerance values, and build habits of deliberation in decision-making in the classroom. Thus, democracy-based learning at the elementary school level is an important foundation in forming a generation that is intellectually and emotionally intelligent.